Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/cid/cir034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guidelines by the Infectious Diseases Society of America for the Treatment of Methicillin-Resistant Staphylococcus aureus Infections in Adults and Children: Executive Summary

Abstract: Evidence-based guidelines for the management of patients with methicillin-resistant Staphylococcus aureus (MRSA) infections were prepared by an Expert Panel of the Infectious Diseases Society of America (IDSA). The guidelines are intended for use by health care providers who care for adult and pediatric patients with MRSA infections. The guidelines discuss the management of a variety of clinical syndromes associated with MRSA disease, including skin and soft tissue infections (SSTI), bacteremia and endocarditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
1,184
1
41

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,443 publications
(1,245 citation statements)
references
References 25 publications
19
1,184
1
41
Order By: Relevance
“…The rate of adequate echocardiography was calculated as the number of patients with echocardiography / the number of patients with complicated bacteremia. Uncomplicated bacteremia was defined according to the Clinical Practice Guidelines of the Infectious Disease Society of America for the treatment of MRSA infections 1. We regarded the cases as uncomplicated bacteremia if they met all of the following criteria: exclusion of endocarditis, absence of implanted prostheses, negative follow‐up blood cultures, defervescence within 72 h of therapy, and absence of evidence of metastatic sites of infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of adequate echocardiography was calculated as the number of patients with echocardiography / the number of patients with complicated bacteremia. Uncomplicated bacteremia was defined according to the Clinical Practice Guidelines of the Infectious Disease Society of America for the treatment of MRSA infections 1. We regarded the cases as uncomplicated bacteremia if they met all of the following criteria: exclusion of endocarditis, absence of implanted prostheses, negative follow‐up blood cultures, defervescence within 72 h of therapy, and absence of evidence of metastatic sites of infection.…”
Section: Methodsmentioning
confidence: 99%
“…Staphylococcus aureus bacteremia (SAB) causes significant morbidity and mortality, and usually causes complications (e.g., infective endocarditis and metastatic abscess). For the prevention and early detection of these complications, US guidelines for methicillin‐resistant S. aureus (MRSA) infection recommended several specific management strategies, particularly follow‐up blood cultures, sufficient treatment duration, and echocardiography 1. Several observational studies have reported that a higher rate of adherence to these recommendations was associated with lower SAB‐related mortality 2, 3…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CF infected with MRSA who are experiencing an acute pulmonary exacerbation, vancomycin and linezolid are the first-line antimicrobial choices (34,35). Dosing of vancomycin is based on the patient's weight and creatinine clearance.…”
Section: Methicillin-resistant Staphylococcus Aureusmentioning
confidence: 99%
“…The most recent guidelines on the treatment of MRSA published by the Infectious Diseases Society of America (IDSA) in 2011 give no information on the importance of an MIC within the susceptible range for clinical decision-making [10,11]. However, these were written in 2010 and evidence has continued to emerge since their inception and subsequent publication.…”
Section: The Vancomycin Breakpointmentioning
confidence: 99%